Ergonomic Evaluation Of Work And Environmental Stress On Operators Working In Multimedia Electronic Chip Manufacturing Factory In Malaysia And Effects Of Implementing Ergonomic Improvements - Hwa, Quek Yeow (2004)
Recent advances in technology have changed the paradigm of working methods/processes, workplaces, working conditions, environment conditions, environment, etc., in manufacturing industries as compare to those during the early decades. These have brought ergonomics/human factors aspects to our immediate attention even though it is still in its stages of infancy in Industrially Developing Countries (IDCs) like Malaysia. Since Multimedia Electronic Chip Manufacturing (MMCM) industry is one of the key economic sectors in Malaysia, MMCM is chosen as the focus of the present study. The company in this industry are aware that employees are the key elements contributing towards the success of their enterprise